2020
DOI: 10.1016/j.sjbs.2020.06.037
|View full text |Cite
|
Sign up to set email alerts
|

APOE2 promotes the development and progression of subretinal neovascularization in age-related macular degeneration via MAPKs signaling pathway

Abstract: Background Neovascular age-related macular degeneration (nvAMD) is one of the main pathological features of wet AMD. Apolipoprotein E2 is involved in the formation of nvAMD but the molecular mechanism has not been reported. Methods The APOE alleles in AMD patients were detected by genotyping. Mouse models were divided into 4 groups according to transfection different gene segments and laser-induced treatment. APOE2, VEGF, PDGF-BB, b-FGF and inflammatory cytokines (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…A large study of a Brazilian population failed to find an association between ApoE2 and AMD [ 225 ]. However, ApoE2 may play a role in the pathogenesis of MNV by upregulating angiogenic factors [ 230 ].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…A large study of a Brazilian population failed to find an association between ApoE2 and AMD [ 225 ]. However, ApoE2 may play a role in the pathogenesis of MNV by upregulating angiogenic factors [ 230 ].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Apolipoprotein E, involved in lipid homeostasis and functioning as a lipid and cholesterol transporter [33], has three allelic variants, from the most frequent to the less frequent in the human body: ApoE3, ApoE4 and ApoE2 [21]. Studies show that among these polymorphisms, the ApoE2 allele increases the risk of developing subretinal neovascularization [34], while ApoE4 seems to be protective [35]. On the contrary, Liutkeviciene et al suggested that ApoE4/E2 genotype could be protective [36], Viturino et al found no impact of ApoE2/E2 genotype on the increased risk of AMD [37], and Fernández-Vega et al described a protective role of ApoE2 allele in wet AMD in a Spanish population [38].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The effects of APOE isoforms on MAPK signaling in human RPE cells and laser-induced nvAMD mouse models expressing human APOE2 isoform were evaluated. Results demonstrated that APOE2 activates MAPKs signalling (p-ERK, p-JNK and p-p38) and induces the up-regulation of downstream target genes including VEGF, PDGF-BB and b-FGF growth factors and pro-inflammatory molecules such as TNF-a, IL-1b and IL-6, leading to retinal inflammation and nvAMD development [ 82 ]. These findings highlight the protective role that the APOE e4 allele plays in AD and the pro inflammatory role in AMD.…”
Section: Introductionmentioning
confidence: 99%